CYTOTOXICITY AND ANTIPROLIFERATION OF PHYCOCYANIN FROM SPIRULINA PLATENSIS EXTRACT ON WIDR COLON CANCER CELL LINE - Putri, Ajeng Kurniasari; Dimarti, Safira Chairani; Yuniati, Renni; Susilaningsih, Neni (Biosaintifika: Journal of Biology & Biology Education, 2020)
Phycocyanin from Spirulina platensis extract has anticancer activity against various types of cancer cell cultures. However study about its effect on colon cancer cell lines, especially the WiDr, has not been reported before. This study aimed to reveal the anticancer activity of phycocyanin from Spirulina platensis extract on WiDr cells. The research was an in vitro experimental study, with the investigation on cytotoxicity also antiproliferation as the anticancer parameters. Both cytotoxicity and antiproliferation test was conducted through MTT assay to observe the visualization and inhibition of proliferation of different concentrations of phycocyanin in several incubation times on the WiDr colon cancer cell line. The obtained data were then processed statistically with the Two Way ANOVA test at a significance value of p <0.05 and followed with the Post Hoc test since there were significant differences. Based on the results, it could be postulated that phycocyanin extracted from freshwater Spirulina platensis was classified as non-toxic (IC50 of 855 µg/ml). Consequently, it is less potential to be used as the treatment for colon cancer. However, phycocyanin could inhibit the proliferation of the WiDr cell for approximately 47.4%, specifically at the concentration of 1710 µg/ml for 72 hours. It could be concluded that freshwater phycocyanin is less effective as an anticancer substance. The benefit of this study is to provide the new scientific evidence of the contrary results of freshwater phycocyanin activity from Spirulina platensis as an anticancer agent of colon cancer.